The Role of the Local Government in Implementing Article 28 E Paragraph 1 of the 1945 Constitution Against the Occurrence of Forced Dissolution of Worship in the Area of Setia Village - Jonatan Marbun; Arsiska Sari; Ali Asdon Tanjung; Parlaungan Gabriel Siahaan; Novridah Reanti Purba (International Journal of Education, Information Technology, and Others, 2023)
This research aims to analyze the aspect of the relationship between Article 28E Paragraph 1 of the 1945 Constitution which regulates freedom of religion with the controversy over the dissolution of the Mawar Sharon Church (GMS) worship in Kelurahan Setia. This research uses a qualitative approach with interview techniques and literature analysis. The number of sources in this study amounted to 4 people. And the results showed that there was no evidence of forced dissolution of GMS as reported, but only a misunderstanding between residents and GMS managers. The Local Government of Kelurahan Setia is considered to have tried to be tolerant and actively perform the function of mediation and monitoring the situation to ease the tension that had occurred.